(S)-4-Isopropyl-5,5-diphenyloxazolidin-2-one - Raffaella Mancuso; Rossana Miliè; Ida Ziccarelli; Mariangela Novello; Nicola Della Ca’; Bartolo Gabriele (Molbank, 2018)
(S)-4-Isopropyl-5,5-diphenyloxazolidin-2-one has been synthesized for the first time by the enantiospecific oxidative carbonylation of commercially available (S)-2-amino-3-methyl-1,1-diphenylbutan-1-ol. The cyclocarbonylation reaction was carried out at 100 °C in 1,2-dimethoxyethane (DME) as the solvent for 15 h, under 20 atm of a 4:1 mixture of CO–air and in the presence of the catalytic system PdI2/KI (substrate:KI:PdI2 molar ratio = 100:10:1), to give the oxazolidinone derivative in 81% isolated yield.